COL2A1 Gene Mutations: Mechanisms of Spondyloepiphyseal Dysplasia Congenita - Nenna, Raffaella (Appl Clin Genet, 2019)
The COL2A1 gene consists of 54 exons spanning over 31.5 kb and encodes for type II collagen. Type II collagen is the main component of hyaline cartilage extracellular matrix, nucleus pulposus of intervertebral discus, vitreous humor of the eye and inner ear structure. Molecular defects in COL2A1 gene cause a wide variety of rare autosomal-dominant conditions known as type II collagenopathies. A clear genotype–phenotype relationship is not yet known. However, some correlations are described. Spondyloephyseal dysplasia congenita was suggested for a short-trunk dwarfing condition affecting primarily the vertebrae and the proximal epiphyses of the long bones.